Oximation reaction induced reduced graphene oxide gas sensor for formaldehyde detection - Lei Zhou; Rong Qian; Shangjun Zhuo; Qiao Chen; Zhaoyin Wen; Guorong Li (Journal of Saudi Chemical Society)
High-performance gas sensors can offer great potentials for monitoring and detection of volatile organic compounds (VOCs) in both domestic and industrial environment. In the present work, a new HCHO gas sensor was constructed with reduced graphene oxide (RGO) induced by the oximation reaction. The gas-sensing performance test results suggested that the RGO hydroxylamine hydrochloride (RGO/HA-HCl) sensor presented a high response of 75% at 16 ppm HCHO at room temperature, and a high selectivity for HCHO suffering little interference with high concentrations of volatile organic compounds, including methanol, ethanol, and methylbenzene, dichloromethane and water. Additionally, the RGO/HA-HCl sensor also showed a good long-term stability with RSD of 5.83% for a 15-day continuous sensing test, and the detection limit (DL) could reach 0.023 ppm under ambient conditions. Moreover, the mechanism for the high sensitivity and selectivity of formaldehyde was further established by in-situ gas chromatography mass spectrometry (GC–MS). This work would provide a reliable new HCHO gas sensor which could be used for monitoring and forewarning the emission of HCHO for a better protection and improvement of our environment. Keywords: Oximation reaction, Reduced graphene oxide, Gas sensor, Formaldehyde, Selectivity